Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Mahasiswa Dalam Memilih Jurusan Administrasi Bisnis Politeknik Negeri Banjarmasin - Maharani, Sari Hepy; Permanasari, Linda; Rohayati, Rohayati (P3M Politeknik Negeri Banjarmasin, 2018)
In any organization, decision making is considered very crucial. Decision making should be based on the information that is considered important as well. This research attempts to analyze the decision-making factors such as the image, interests, collective decision, availability of employment, facility, price, place and promotion for choosing Business Administration as major choice Polytechnic. This study is also expected to provide some information as the input for all parties who are interested in this crucial problem. The sample used was taken from the students of Business Administration . The questionnaires were distributed to them and then 158 copies of them were analyzed by factor analysis nd regression. Based on the analysis, it was found that there are seven variables considered by students in choosing major department ; facilities and infrastructure, images, promotions, joint decisions, availability of employment, location and request. And from all variables, the variables that have significant influence are joint promotions and decisions. And the joint decision variable is identified as the variable that has the most influence on the decision to choose a study program.